Neural compensation during a novel operant devaluation task in rats - Fisher, Hayley (Kansas State University, 2020)
Reinforcer devaluation is a task often used to model flexible goal-directed action, the ability to adaptively modify behavior when the value of a reinforcer changes. Deficits in goal-directed action are reported in multiple neuropsychiatric conditions, including schizophrenia. We designed a novel devaluation task in which goal-directed action could be guided by stimulus-outcome (S-O) [presumably orbitofrontal cortex (OFC)-mediated] or response-outcome (R-O) associations [presumably prelimbic cortex (PL)-mediated] to maintain. Therefore, if our task is able to model neural compensation, damage to either PL or OFC should not impair devaluation because the non-damaged region can compensate for the loss using the alternate strategy. Additionally, we investigated whether the mediodorsal thalamus (MD) may be involved in neural compensation between these regions as MD is important for directing attentional resources to relevant stimuli in the environment. In Experiment 1, male and female rats (n = 59) received pre-training bilateral OFC, PL, combined OFC+PL, or sham lesions and then completed our devaluation task. Sham, OFC, and PL lesioned rats showed intact devaluation, whereas the OFC+PL lesion group exhibited impaired devaluation. In Experiment 2, male and female rats (n = 20) received pre-training bilateral PL or sham lesions and a unilateral infusion of cholera-toxin b (CTb), a retrograde tracer. Rats were perfused 75 minutes after the beginning of the final session of cued-trial training when Arc protein expression, an early immediate gene indicative of neural activity, is highest following neural activity. We double-labeled brains for Arc and CTb and assessed how PL lesions affected the number of Arc+ neurons in OFC and MD to assess changes in gross neural activity and the percent of CTb+ neurons that were also Arc+ in MD to assess how MD->OFC projecting neurons altered activation patterns when PL was lesioned. We found increased Arc+ neuron in OFC in PL lesioned rats, no change in Arc+ neurons in MD, and a higher proportion of double-labeled neurons in MD. Our results suggest that our devaluation task can successfully model compensation between OFC and PL. Further, it shows that when PL is inactive, OFC increases neural activity, suggestive of the S-O strategy being learned. In addition, it suggests that MD may be involved in modulating which region is active and primarily used to guide learning. This research demonstrates a method to study how functional neural circuitry is subtly altered like in early stages of schizophrenia.
Keywords: Devaluation; Orbitofrontal cortex; Prelimbic cortex; Mediodorsal thalamus; Compensation